Lightweight electric/hybrid vehicle design - Hodkinson, Ron. (Butterworth-Heinemann, 2001)
Lightweight Electric/Hybrid Vehicle Design, covers the particular automotive design approach required for hybrid/electrical drive vehicles. There is currently huge investment world-wide in electric vehicle propulsion, driven by concern for pollution control and depleting oil resources. The radically different design demands of these new vehicles requires a completely new approach that is covered comprehensively in this book. The book explores the rather dramatic departures in structural configuration necessary for purpose-designed electric vehicle including weight removal in the mechanical systems. It also provides a comprehensive review of the design process in the electric hybrid drive and energy storage systems. Ideal for automotive engineering students and professionals Lightweight Electric/Hybrid Vehicle Design provides a complete introduction to this important new sector of the industry. comprehensive coverage of all design aspects of electric/hybrid cars in a single volume packed with case studies and applications in-depth treatment written in a text book style (rather than a theoretical specialist text style).